2018
DOI: 10.1038/s41386-018-0105-x
|View full text |Cite
|
Sign up to set email alerts
|

Profiling changes in cortical astroglial cells following chronic stress

Abstract: Recent studies have suggested that cortical astroglia play an important role in depressive-like behaviors. Potential astroglial contributions have been proposed based on their known neuroplastic functions, such as glutamate recycling and synaptic plasticity. However, the specific mechanisms by which astroglial cells may contribute or protect against a depressive phenotype remain unknown. To delineate astroglial changes that accompany depressive-like behavior, we used astroglial-specific bacTRAP mice exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 72 publications
(63 reference statements)
7
35
1
Order By: Relevance
“…Stress and depression can enhance PNN deposition and also render PNNs resistant to proteolysis (Pantazopoulos et al, 2015;Riga et al, 2017;Simard et al, 2018). Both processes can increase overall PNN levels.…”
Section: Schematic; Hypothetical Changes In Pnn Deposition and Mmp-9 mentioning
confidence: 99%
“…Stress and depression can enhance PNN deposition and also render PNNs resistant to proteolysis (Pantazopoulos et al, 2015;Riga et al, 2017;Simard et al, 2018). Both processes can increase overall PNN levels.…”
Section: Schematic; Hypothetical Changes In Pnn Deposition and Mmp-9 mentioning
confidence: 99%
“…SYNPO2 was demonstrated to closely associate with cognitive development in mice brain [59]. Chronic variable stress in mice induced signi cantly down-regulation of SYNPO2 which was necessary for synaptic plasticity, learning and memory [59]. Although there is less evidence to link caffeine consumption to SYNPO2 expression change, our result suggests that caffeine may in uence the intelligence by affecting the expression of SYNPO2 in human brain.…”
Section: Discussionmentioning
confidence: 70%
“…The GWASdb SNP-Phenotype association dataset showed that SYNPO2 was associated with the schizophrenia phenotype in GWAS datasets [58]. SYNPO2 was demonstrated to closely associate with cognitive development in mice brain [59]. Chronic variable stress in mice induced signi cantly down-regulation of SYNPO2 which was necessary for synaptic plasticity, learning and memory [59].…”
Section: Discussionmentioning
confidence: 99%
“…In order to conceptualize the overall anxiety and depressive phenotype, we included a total “emotionality score” that we have previously employed and was first described by the Sibille laboratory [ 24 , 27 ]; a significant increase in emotionality was induced by stress, which was reduced in fluoxetine-treated stressed WT mice ( Fig 5A ). No effect of fluoxetine was seen in FGF2KOs.…”
Section: Resultsmentioning
confidence: 99%
“…The emotionality score was derived as previously described in Guilloux (2011) [ 24 ]. Z scores were calculated for each test and normalized for locomotor behavior, as appropriate.…”
Section: Methodsmentioning
confidence: 99%